Penggunaan Metode Copula Gaussian untuk Menentukan Nilai Value at Risk Investasi Saham pada Bank BCA dan Bank BRI - Palungan, Kevin Ekarinaldo; Kalondeng, Anisa; Ilyas, Nirwan (Hasanuddin University, 2025)
Investment is capital for one or more assets over a long period of time to obtain profits. Besides being able to provide profits, stock investment also contains an element of risk. Therefore, risk measurement needs to be done so that the risk is within a controlled level so as to reduce the occurrence of investment losses. This study uses the Gaussian Copula to calculate Value at Risk on the closing price data of PT. Bank Central Asia Tbk and PT. Bank Rakyat Indonesia Tbk for the period January 02, 2020 to December 30, 2022. For the Kendall's correlation value τ=0.3307 produces a Pearson correlation value of ρ=0.4965 which is also used as an estimate of the Copula Gaussian parameter. The results of the VaR calculation on a portfolio with a weight of 50% shares of PT Bank Central Asia Tbk and 50% shares of PT Bank Rakyat Indonesia Tbk average VaR at the 95% confidence level of -0.0269 means that if investors invest their funds by 50% in PT Bank Central Asia Tbk shares and 50% in PT Bank Rakyat Indonesia Tbk shares there is a risk that the maximum loss is 2.69% of the invested funds.